Direct anchoring of platinum nanoparticles on nitrogen and phosphorus-dual-doped carbon nanotube arrays for oxygen reduction reaction. (10th March 2015) - Zhu, Jinliang; He, Guoqiang; Liang, Lizhe; Wan, Quan; Shen, Pei Kang
Graphical abstract: Abstract: A novel and facile strategy has been developed to synthesize nitrogen and phosphorus-dual-doped carbon nanotube (N, P-CNT) array and used as Pt support for fuel cell application. In this strategy, the N, P-CNT array with well-designed nanostructure is directly grown on the cheap Ni foam using self-generated cylindrical Ni2 P as catalysts. The N, P-CNT with open ends and a large hollow channel provides large number of reactive sites in inner walls with access to reactants compared with conventional bamboo-shape nitrogen-doped carbon nanotubes (N-CNTs). The N, P-CNTs which possess abundant disordered nanostructures and reaction active sites can ingeniously anchor Pt with no need of pretreatment. The highly distributed Pt nanoparticles provide well Pt utilization and strengthen interaction between N, P-CNTs and Pt nanoparticles. The synthesized Pt/N, P-CNTs catalyst shows much better electrocatalytic performance for oxygen reduction reaction in comparison with Pt/CNTs, Pt/N-CNTs and commercial Pt/C catalysts. At 0.9 V vs . RHE in 0.1 mol L −1 HClO4, the Pt mass activity of Pt/CNTs and Pt/N-CNTs are 93.5 and 165.4 mAmg −1 Pt, while, the Pt/N, P-CNTs catalyst shows a mass activity of 285.3 mA mg −1 Pt, which is 3.1 and 1.7 times as high as that of Pt/CNTs and Pt/N-CNTs, respectively.